Targeting vascular leakage in lung inflammation - Li, Liang (2016)
The 2009 outbreak of H1N1 caught many off guard-not least those responsible for tracking the emergence of new influenza strains and outbreaks [1]. Although the influenza A H1N1 pandemic in 2009 proved relatively mild, it still claimed over 14,000 lives across the globe. Given the relentless and rapid mutation of influenza viruses, predicting the onset of pandemics is virtually impossible. Moreover, the development of effective vaccines and antiviral agents against this renegade RNA virus also lags behind the emergence of new influenza strains. Hence, there is considerable interest in strategies that target host responses to combat influenza infection and pneumonia to counter the occurrence of antiviral-resistant strains.